Nanoindentation Of Graphene Reinforced Epoxy Resin As A Conductive Ink For Microelectronic Packaging Application - Salim, Mohd Azli; Omar, Ghazali; Masripan, Nor Azmmi; Md. Saad, Adzni; Sudin, Mohd Nizam; Mokhlis, Maizura; Caridi, Francesco (Universiti Malaysia Perlis, 2020)
Conductive ink is a special type of ink which allows current to flow through the ink. There are several varieties of conductive inks in the market and it is crucial to choose a suitable ink for the electronic applications. Graphene material is chosen to replace the current ink due to its promising properties that have been explored by many researchers. This paper aims to investigate the effect of temperature and percentage of graphene ink on hardness and Young's modulus of printed graphene ink samples. Samples were fabricated using a simple method involving formulating, mixing, printing and curing processes and the ink was printed on the glass slide substrate. The samples were cured at 160°C and 180°C for one hour. The mechanical properties of printed graphene ink sample were evaluated using Dynamic Ultra Micro Hardness (DUMH). All the measurements were done with the same force of indentation to avoid the possibility of perforation of printed graphene ink. The results show that higher curing temperature and percentage of filler loading give bigger Young’s modulus and hardness of the printed graphene ink sample.